Early endoscopic, laboratory and clinical predictors of poor disease course in paediatric ulcerative colitis. Issue 4 (21st May 2014) - Schechter, Amir; Griffiths, Christopher; Gana, Juan Cristóbal; Shaoul, Ron; Shamir, Raanan; Shteyer, Eyal; Bdolah-Abram, Tali; Ledder, Oren; Turner, Dan
Abstract : Objective: Data to support treatment algorithms in ambulatory paediatric UC are scarce. We aimed to explore the 1 year outcome in an inception cohort of paediatric UC patients and to identify early predictors of good outcome that might serve as short term treatment targets. Design: A chart review of 115 children with new onset UC was performed (age 11±4.1 years; 58 (50%) males; 86 (75%) extensive colitis; 70 (61%) moderate–severe disease; 63 (55%) received steroids at baseline). We assessed the Paediatric Ulcerative Colitis Activity Index (PUCAI) and laboratory variables at the time of diagnosis and at 3 months, and endoscopy at diagnosis. Results: The 3 month PUCAI was the strongest predictor of 1 year sustained steroid free remission (SSFR) (area under the receiver operating characteristic curve (AUROC)=0.7 (95% CI 0.6 to 0.8) and colectomy by 2 years (AUROC=0.75 (0.6 to 0.89)). SSFR was achieved in 9/54 (17%) children who had active disease (PUCAI ≥10) at 3 months (negative predictive value (NPV)=83%) and by 4/46 (8.6%) of those with a PUCAI score >10; (NPV=91%, positive predictive value=52%; p<0.001), implying that PUCAI >10 at 3 months has a probability of 9% for achieving SSFR versus 48% with a PUCAI value of ≤10. None of the variables at baseline was predictive of SSFR or colectomy (endoscopic severity, disease extent, age, PUCAI or C reactive protein/erythrocyte sedimentation rate/albumin/haemoglobin; all AUROC<0.6, p>0.05) but baseline PUCAI predicted subsequent acute severe colitis and the need for salvage medical therapy. Conclusions: Completeness of the early response appears more important than baseline UC severity for predicting outcome in children, and supports using PUCAI<10 as a feasible treatment goal. Our data suggest that treatment escalation should be considered with a PUCAI value of ≥10 at 3 months.